Legal Construction against Customer Deposit Protection as a Result Liquidity of PT Bank Perkreditan Rakyat Mustika Utama Kolaka - Ashadi L. Diab; Rizal Darwis; Asni Zubair; Sitti Selamita (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
This article discusses the protection of customer deposits of PT. Bank Perkreditan Rakyat (BPR, rural bank) Mustika Utama Kolaka. This type of research is descriptive and qualitative with data collection methods using observation, interviews, and documentation. The research data is categorized into primary data and secondary data, processed and analyzed through data reduction steps, data presentation, and conclusion drawing with an analytical descriptive approach. The results showed that the procedure carried out by the Financial Services Authority (OJK) in the process of expiring PT. BPR Mustika Utama Kolaka's license was to carry out direct and indirect supervision of the bank. OJK after declaring its business license revoked, the handling of customer deposit protection is carried out based on the procedures established by the Indonesia Deposit Insurance Corporation (IDIC) by referring to Law Number 21 of 2011 concerning the Financial Services Authority. On the other hand, in terms of the legal construction of conflict resolution between customers and the bank, it prioritizes steps to acculturate local wisdom and actualize legal culture in the local community.